Pengaruh Digital Marketing Dalam Strategi Customer Relation Management di PT. Indofood Sukses Makmur, Tbk - Ade Irma Yesa Andini; Dyva Putri Trivia; Galang Berlyne Ramadhan; Laila Mufida (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research discusses the role of digital marketing and customer relationship management at PT. Indofood Sukses Makmur Tbk, a company mostly engaged in food and beverages that grows and originates from Indonesia. This research uses qualitative methods. The data collection method used in this study is a descriptive method which is a data collection technique via the internet. The results of the study concluded that digital marketing has a significant influence on customer relationship management strategies at PT. Indofood Sukses Makmur Tbk. Digital marketing plays a crucial role in expanding the company's market area and target customers, as can be seen from the use of various digital platforms to promote products, such as Instagram, Twitter, Tiktok, and Facebook. Therefore, digital marketing and CRM have an important role in developing strategies that can maintain the competitive advantage of PT. Indofood Sukses Makmur Tbk.